Wilson, Reginald: my Air Force recollections (April 25, 2007) ... - Unav (University of Victoria Libraries, 2022)
ABSTRACT: Reginald Wilson Reginald Wilson.mp3 0:00 When I was one year old. I was a Wilson Loudmouth. All of us Wilson's are big mouthed. Anyhow, to give the people a little peace and relaxing my mother took me out to the beach, which was about 50 yards away. There was a dead whale on the little bay there near Quathiaski Cove. Anyhow, there was a dead whale on the beach. So I'm "Kloqsiway" (Indian Name) that's the name she gave me. Which means dead whale on the beach. Now she could have given me "Maxinukw" which is killer whale. I dunno. I didn't like that. I'm "Kloqsiway". I'm Dead Whale on the beach. If you see me walking across the street don't say 'Hey Dead Whale on the Beach' 'cuz I always have my bingo dabber on me, you'll get crowned. My name is "Kloqsiway". I am "Kloqsiway." In my heart I am "Kloqsiway" (not Maxinukw) I would have liked to have been. So that's how I got my name. 1:53 My Christian name is Reginald Gilbert Wilson. The Missionaries gave us that name to try and save our wretched souls. ... : Interviewer: Wood, Jessica D. ...